Ecocriticism-Based Curriculum Development Strategies in Indonesia Universities: Evaluation and Recommendations - Al Masjid, Akbar; Pamungkas, Onok Yayang (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The purpose of this study is to evaluate efforts to develop an ecocriticism-based curriculum in various universities in Indonesia and measure the effectiveness of these interventions in improving student understanding. The research method uses mixed methods. The study results show that lecturer training programs, curriculum changes, resource increases, and the use of technology contribute significantly to the improvement of understanding of literary ecocriticism. For this, universities with better curriculum quality and higher lecturer competence tend to produce better understanding among students. Universities with more faculty training programs and more intensive curriculum changes show a higher increase in understanding among students. In particular, leading universities investing in extensive faculty training programs and periodic curriculum revisions show more positive results than universities undertaking such interventions. Thus, this study shows that investment in lecturer training and increased access to literary resources are essential for successfully integrating ecocriticism into the literary curriculum.